1992
DOI: 10.1017/s0950268800049700
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and control of an outbreak of typhoid in a psychiatric institution

Abstract: An outbreak of typhoid caused by Salmonella typhi of the same Vi-phage type (D1) and of the same antibiogram was reported in a large psychiatric institution in Singapore. A total of 95 (4.8%) of the 1965 inmates were infected, 47 with symptoms and 48 asymptomatic. Transmission was through close person-to-person contact and not through contaminated food or water. The source of infection could not be established. The outbreak was brought under control by maintaining a high standard of environmental sanitation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…He could have contracted typhoid when he had visited PNG 10 months previously and become a S. typhi carrier. Although his father did not recall any illness consistent with S. typhi infection, epidemiological studies during typhoid outbreaks have shown that up to half of S. typhi infections may be asymptomatic 9 . However, S. typhi was not present in the father's stools when tested shortly after the patient's discharge (although there is the remote possibility that he had spontaneously cleared carriage after transmitting the bacteria to his son).…”
Section: Discussionmentioning
confidence: 97%
“…He could have contracted typhoid when he had visited PNG 10 months previously and become a S. typhi carrier. Although his father did not recall any illness consistent with S. typhi infection, epidemiological studies during typhoid outbreaks have shown that up to half of S. typhi infections may be asymptomatic 9 . However, S. typhi was not present in the father's stools when tested shortly after the patient's discharge (although there is the remote possibility that he had spontaneously cleared carriage after transmitting the bacteria to his son).…”
Section: Discussionmentioning
confidence: 97%
“…Sears et al (92) may have underestimated the sensitivity, since the period of sampling may not have in fact coincided with deposition of S. Typhi into the sewer by the carrier, particularly if shedding was intermittent or if the carrier did not use the connected toilet during the sampling period. In cases of institutional sewage surveillance (e.g., hospitals and prisons), disinfectants may diminish sensitivity of the culture-based bacteriology (93).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Outbreaks of Salmonella enteritis in psychiatry units have been reported from several countries ( ). [29][30][31][32][33] Outbreaks occurred through close person-to-person contact [29,32,33] or because of contamination of food. [29,30] Management Recommendations.The identification of the asymptomatic reservoir of Salmonella by rectal swabbing is a major approach in controlling outbreaks.…”
Section: Salmonella Speciesmentioning
confidence: 99%